2016
DOI: 10.1177/1747954116667110
|View full text |Cite
|
Sign up to set email alerts
|

The acute effect of maximal voluntary isometric contraction pull on start gate performance of snowboard and ski cross athletes

Abstract: 19This study investigated whether adding a maximal voluntary isometric contraction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…In addition, for snowboard cross, taller and heavier athletes have an advantage when they come into contact or collide with their opponents during the competition. Haycraft et al (14) and Spasić et al (31) confirmed that a heavier athlete could increase the normal force resulting in higher friction, which will reduce snowboarding athletes' velocity, but higher body mass would also produce a higher Fg sinα component at the same time, which is bigger than the increase in friction (Figure 2). Therefore, under the same conditions, athletes with heavier mass glide faster, and the results are better.…”
Section: Resultsmentioning
confidence: 91%
“…In addition, for snowboard cross, taller and heavier athletes have an advantage when they come into contact or collide with their opponents during the competition. Haycraft et al (14) and Spasić et al (31) confirmed that a heavier athlete could increase the normal force resulting in higher friction, which will reduce snowboarding athletes' velocity, but higher body mass would also produce a higher Fg sinα component at the same time, which is bigger than the increase in friction (Figure 2). Therefore, under the same conditions, athletes with heavier mass glide faster, and the results are better.…”
Section: Resultsmentioning
confidence: 91%
“…Therefore, the aim of this study was to determine the acute effects of different types of strength exercises including plyometrics in fast (FSSC) and slow (SSSC) stretch-shortening cycle exercises, dynamic (DYN) and isometric (ISOM) strength exercises performed during one session on subsequent balance [center of pressure surface area (CoP SA) and velocity (CoP V)] performance in young weightlifters. With reference to the relevant literature ( Twist et al, 2008 ; Haycraft et al, 2016 ; Pancar et al, 2017 ), we hypothesized that the implementation of plyometric and dynamic strength exercises would lead to acute performance enhancements in measures of balance in youth weightlifters. Given that the performance of plyometrics particularly in FSSC affords high levels of postural control to successfully perform the exercise ( Bobbert et al, 1987 ; Komi et al, 1987 ; Kibele et al, 2014 ; Lauber et al, 2021 ), we speculated that FSSC would elicit the greatest changes in subsequent balance performance in youth athletes.…”
Section: Introductionmentioning
confidence: 99%